The Struggle with Irreverent Time in Jamaica Kincaid’s Lucy (Papers in Arts and Humanities, 2022)
Jamaica Kincaid’s lacunary pseudo-autobiography presents the protagonist’s first year in exile and dissects its stages to such an extent that the story takes the form of a photographic slideshow. The unnamed city (presumably New York) appears as a palimpsest locale, almost obliterated by Lucy’s invasive and strikingly detailed memories. This incursion of “space past” and “time past” in the narrative present forecloses an accurate reading of the space and time of her exile. In the end, Lucy becomes well aware of this existential dilemma that suspends her between the past—an unhealed wound—and the present—an unknown territory. Almost the entire book depicts the narrator’s struggle to reconcile the dichotomous cyclical and linear temporalities, each with their corresponding spatial referent: the native island and the city. The present paper analyzes Lucy’s first year in exile as a time loop which closes with a creative reconciliation with the past and appropriation of the linear present.
Keywords: time; space; exile; memory; identity